The Effect Onion Biowaste and NPK Fertilizer of Combinations on Yield and Mineral Content of Mustard (Brassica parachinensis) - Samsuri, Shampazuraini; Dolhaji, Noer Hartini; Abdullah, Nur Suraya; Manaf, Maizahtul Husna Abd (AGRIVITA Journal of Agricultural Science, 2024)
Recent studies have tended to reduce the added quantities of mineral fertilizers by using strategies of combination both organic and chemical. Thus, the effect of a combination of organic and chemical fertilizer was studied from March until August 2023 to investigate the growth, yield and mineral content of mustard as affected by onion biowaste and NPK fertilizer. This experiment was carried out with 5 different treatments and 4 replications, utilizing the Randomized Complete Block Design (RCBD). The treatments consisted of a control with 100% NPK fertilizer (T0), 100% peel onion fertilizer (T1), 50% NPK fertilizer + 50% peel onion (T2), 30% NPK fertilizer + 70% peel onion (T3), 70% NPK fertilizer + 30% peel onion fertilizer (T4). The parameters evaluated in this experiment included plant height, number of leaves, plant fresh weight, and NPK content in the leafy parts. The results showed that there were significantly higher in all studied parameter when using combination of 50% NPK fertilizer + 50% peel onion (T2) compared to the other combinations. Hence, it can be concluded that the combination of NPK fertilizer and peel onion fertilizer is a promising approach to reduce chemical fertilizer application and increase the quality of crops.